2019
DOI: 10.1017/s0022149x19000737
|View full text |Cite
|
Sign up to set email alerts
|

Redescription ofAcanthogyrus(Acanthosentis)maroccanus(Dollfus, 1951) (Acanthocephala: Quadrigyridae), a parasite of the Algerian barbLuciobarbus callensis(Valenciennes) (Cyprinidae) in Algeria, and first molecular data

Abstract: Acanthogyrus (Acanthosentis) maroccanus (Dollfus, 1951), an insufficiently described quadrigyrid acanthocephalan of cyprinid fishes from Northwest Africa, is redescribed based on recently collected specimens from the Algerian barb Luciobarbus callensis (Valenciennes) in Algeria. Newly observed morphological features for A. (A.) maroccanus include the arrangement of proboscis hooks (not in regular circles), the male reproductive structures extending into the copulatory bursa and the presence of a para-receptacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…Menasria et al presented that A. maroccanus forms a poorly supported clade within the Eoacanthocephala based on 28S rDNA gene phylogenetic analysis [10]. In present study, no intraspecifc genetic divergence was found among the different isolates of A. kashmirensis regarding 18S and ITS1-5.8S-ITS2 rDNA sequences.…”
Section: Discussioncontrasting
confidence: 49%
“…Menasria et al presented that A. maroccanus forms a poorly supported clade within the Eoacanthocephala based on 28S rDNA gene phylogenetic analysis [10]. In present study, no intraspecifc genetic divergence was found among the different isolates of A. kashmirensis regarding 18S and ITS1-5.8S-ITS2 rDNA sequences.…”
Section: Discussioncontrasting
confidence: 49%
“…Molecular methods are an important tool for morphological identification, diversity and taxonomic relationships among acanthocephalan species (García-Varela et al ., 2017, 2019; Li et al ., 2018; Amin et al ., 2019a, b, c; Lisitsyna et al ., 2019; Menasria et al ., 2019; Sharifdini et al ., 2020). The phylogenetic relationships and systematic position of Pallisentis are poorly explored compared to other genera.…”
Section: Discussionmentioning
confidence: 99%
“…(A.) maroccanus Dollfus, 1951 [33] sequence collected from a specimen found in barb Luciobarbus callensis from Algeria (MK953673 [70]) only encompasses the D1-D3 regions of the 28S rRNA gene and differed by 16% based on a 757-bp alignment. The 28S rDNA sequence in GenBank of A.…”
Section: Molecular Identification Of the Acanthocephalanmentioning
confidence: 99%
“…Acanthogyrus (A.) maroccanus, is known from several barb fish species and is considered endemic in North Africa [33,68,70]. Specimens of this species have significantly larger anterior, middle, and posterior proboscis hooks (62 lm, 62 lm, 48 lm, respectively) and only 12-18 rows of spines on the body (see redescription [70]), and our 28S rRNA gene sequences differed from the A.…”
Section: Remarksmentioning
confidence: 99%